2022
DOI: 10.1021/acsomega.2c05605
|View full text |Cite
|
Sign up to set email alerts
|

Green-Based Approach to Synthesize Silver Nanoparticles Using the Fungal Endophyte Penicillium oxalicum and Their Antimicrobial, Antioxidant, and In Vitro Anticancer Potential

Abstract: A green-based approach for the synthesis of silver nanoparticles has gained tremendous attention in biomedical applications. Fungal endophytes have been recognized as a remarkable biological source for the synthesis of potential nanodrugs. The present study focuses on the fabrication of silver nanoparticles using the fungal endophyte Penicillium oxalicum (POAgNPs) associated with the leaf of the Amoora rohituka plant. Sharp UV–visible spectra at 420 nm appeared due to the surface plasmon resonance of POAgNPs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 104 publications
2
17
0
Order By: Relevance
“…6,57 The phenolic and flavonoid content present in EA extract of C. gloeosporioides confer anticancer activity and have been shown in our previous studies. 21,58 The present study thus validated the apoptosis-inducing potential of PEA, purified from mixture of bioactive compounds present in the EA extract of C. gloeosporioides. The compound PEA has long been reported for its activity against cancer cell proliferation.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…6,57 The phenolic and flavonoid content present in EA extract of C. gloeosporioides confer anticancer activity and have been shown in our previous studies. 21,58 The present study thus validated the apoptosis-inducing potential of PEA, purified from mixture of bioactive compounds present in the EA extract of C. gloeosporioides. The compound PEA has long been reported for its activity against cancer cell proliferation.…”
Section: Discussionsupporting
confidence: 71%
“…[17][18][19] Besides, various studies have reported the anticancer potential of biologically engineered silver nanoparticles mediated by fungal endophytes. 20,21 Whereas, due to its small size, the nanoparticle of silver can easily enter the bloodstream and may induce toxicity to many organs, including the brain, spleen, heart, liver, and kidney by altering various physiological and biochemical parameters. 22 On the other hand, the phenolic compounds, phytoestrogens, polyketides, flavonoids, terpenes, terpenoids, steroids, and carotenoids produced from fungal endophytes have remarkable immunological and physiological effects with low toxicity as compared to synthetic drugs.…”
Section: Introductionmentioning
confidence: 99%
“…DAPI, a fluorescence dye staining was used to evaluate the presence of apoptotic cells and nuclear morphology of breast cancer cells MDA-MB-231 and MCF-7 treated with the EA extract of C. gloeosporioides . Briefly, the human breast cancer cells, MDA-MB-231 and MCF-7, were seeded in a six-well plate containing a coverslip at a density of 1 × 10 5 cells and treated with the EA extract of C.…”
Section: Methodsmentioning
confidence: 99%
“…The cytotoxic activity of the EA extract of C. gloeosporioides was performed using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay. 26 Invasive ductal/breast carcinoma cells, MDA-MB-231 and MCF-7, were grown in Dulbecco’s modified Eagle’s medium (Himedia) with 10% heat-inactivated fetal bovine serum (HI-FBS, Thermo Fisher Scientific) in a T-25 flask and were passaged using trypsin–EDTA (Himedia, TCL034) upon 80–90% of cell confluency. The cells were maintained in a 5% CO 2 incubator at 37 °C and observed daily for cellular morphology and the presence of any contaminations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation